2005
DOI: 10.1038/sj.sc.3101762
|View full text |Cite
|
Sign up to set email alerts
|

Continual supplementation with n-3 fatty acids does not modify plasma lipid profile in spinal cord injury patients

Abstract: Study design: A prospective study during a diet modification. Objective: To observe the evolution of the plasma lipid profile in a group of spinal cord injury (SCI) patients given a supplement of a mixture of docosahexanoic acid (DHA) and eicosapentaenoic acid (EPA). Setting:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…29,83,84 Six months of omega-3 FA administration in a cohort of 19 men with SCI resulted in a 10-fold increase in plasma omega-3 FA values, but did not affect lipid profile. 85 However, the 2.25 g/day of omega-3 FA provided in this study may have been below the effective supplement dose range, which has been suggested to be 3-5 g/day. 86 Given the wide variety of proposed beneficial effects of omega-3 FA including lowering of TG, hypertension, and atherosclerotic plaque formation, 29,87,88 future investigations with more applicable dosing appear warranted.…”
Section: Nutritional Recommendationsmentioning
confidence: 80%
“…29,83,84 Six months of omega-3 FA administration in a cohort of 19 men with SCI resulted in a 10-fold increase in plasma omega-3 FA values, but did not affect lipid profile. 85 However, the 2.25 g/day of omega-3 FA provided in this study may have been below the effective supplement dose range, which has been suggested to be 3-5 g/day. 86 Given the wide variety of proposed beneficial effects of omega-3 FA including lowering of TG, hypertension, and atherosclerotic plaque formation, 29,87,88 future investigations with more applicable dosing appear warranted.…”
Section: Nutritional Recommendationsmentioning
confidence: 80%
“…[592829] Recent studies in normal volunteers indicate that the beneficial effects of dietary PUFA on risk of chronic inflammatory disease (cardiovascular disease, rheumatoid arthritis, asthma, and periodontitis)[510] is based on decrease in production of interleukins. [9]…”
Section: Discussionmentioning
confidence: 99%
“…In a previous and unique interventional study,[10] Javierre et al . evaluated the possible effect of n-3 PUFA (1.5 g of DHA and 0.75 g of EPA) on plasma lipid profile in 19 adult males with SCI for 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…10 Metabolic syndrome, including high blood pressure, hyperglycemia, dyslipidemia, and central adiposity, is more common in individuals with SCI than the general population. 6,[11][12][13][14][15][16][17] Consequently, SCI patients have increased risk of heart disease, stroke and diabetes, 13,[18][19][20][21][22][23] and increased morbidity and mortality compared with the general population. 6,12,13,19,20 Understanding why metabolic syndrome is more prevalent in the SCI population is an important clinical goal that requires a better understanding of what drives post-SCI organ responses.…”
Section: Introductionmentioning
confidence: 99%